2008
DOI: 10.1002/lt.21397
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-free, tacrolimus-basiliximab immunosuppression in pediatric liver transplantation: Clinical and pharmacoeconomic study in 50 children

Abstract: Corticosteroid-free immunosuppression (IS) may be potentially beneficial for transplanted patients, particularly children. The purpose of this study was to evaluate the efficacy and cost of such strategy in primary pediatric liver transplantation (LT). Fifty pediatric LT recipients were prospectively treated with a steroid-free, tacrolimus-basiliximab-based IS (group TB). A group of 34 children transplanted under a conventional tacrolimus-steroids regimen served as control series (group TS). Groups TB and TS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
5
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 21 publications
7
75
5
1
Order By: Relevance
“…Other explanations for the worse univariable outcomes in the MS group indude a higher proportion of African Americans, a higher proportion of patients who underwent transplantation in the earlier era, and a higher proportion of patients with a previous sternotomy, all of which have been associated with a higher risk of graft loss (1, 9, 10). The successful use of SF maintenance immunosuppression in our analysis is consistent with single-center and dual-center reports of SF maintenance immunosuppression in heart, liver, and renal transplantation (2, 3, 11, 12). While there are no other studies in pediatric HT directly comparing graft survival in patients with and without MS use, multiple single-center studies of pediatric HT have reported outcomes with an SF maintenance immunosuppression protocol with excellent results (2, 8, 13-16).…”
Section: Discussionsupporting
confidence: 88%
“…Other explanations for the worse univariable outcomes in the MS group indude a higher proportion of African Americans, a higher proportion of patients who underwent transplantation in the earlier era, and a higher proportion of patients with a previous sternotomy, all of which have been associated with a higher risk of graft loss (1, 9, 10). The successful use of SF maintenance immunosuppression in our analysis is consistent with single-center and dual-center reports of SF maintenance immunosuppression in heart, liver, and renal transplantation (2, 3, 11, 12). While there are no other studies in pediatric HT directly comparing graft survival in patients with and without MS use, multiple single-center studies of pediatric HT have reported outcomes with an SF maintenance immunosuppression protocol with excellent results (2, 8, 13-16).…”
Section: Discussionsupporting
confidence: 88%
“…Other explanations for the worse univariable outcomes in the MS group indude a higher proportion of African Americans, a higher proportion of patients who underwent transplantation in the earlier era, and a higher proportion of patients with a previous sternotomy, all of which have been associated with a higher risk of graft loss (1,9,10). The successful use of SF maintenance immunosuppression in our analysis is consistent with single-center and dual-center reports of SF maintenance immunosuppression in heart, liver, and renal transplantation (2,3,11,12). While there are no other studies in pediatric HT directly comparing graft survival in patients with and without MS use, multiple single-center studies of pediatric HT have reported outcomes with an SF maintenance immunosuppression protocol with excellent results (2,8,(13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 84%
“…Anti-IL-2 receptor antibodies are now widely used in liver transplantation as induction agents targeted at reducing the incidence of ACR (2,17,18) or as a calcineurin-inhibitor (19) or steroid-sparing strategy (20,21) to protect renal function in the immediate postoperative period. Comparison of induction therapy (12) between antithymocyte globulin + cyclosporine + steroid + azathioprine and anti-IL-2 receptor antibody + tacrolimus + steroid + azathioprine demonstrated a reduced ACR incidence in the anti-IL-2 receptor antibody group (43% versus 29%; p < 0.01).…”
Section: Resultsmentioning
confidence: 99%